Unmasking factors affecting sleep pattern disturbances among patients undergoing hemodialysis: A cross-sectional study - Hala Sanad; Khaldoon Al-Roomi; Zahra Abdlmjeed; Mariam Ebrahim; Omar Al Omari; Rasha Eweida; Mohamed Elsehrawy; Khulood Alasfoor; Yusuf Altahoo; Eshrak Hashem; Ahmed El-Monshed; Magda Bayoumi (PLoS ONE, 2026)
Background The number of patients on hemodialysis is steadily increasing in Gulf Arab countries, including Bahrain. Such treatment modality has a negative impact on the quality of life, particularly sleep quality. This study aimed to assess the factors affecting the sleep pattern disturbances of hemodialysis patients in Bahrain. Materials and Methods A cross-sectional design was employed. A convenience sample of 174 patients was recruited to the study from one of the main dialysis centers in Bahrain. Data was obtained via the Pittsburgh Sleep Quality Index questionnaire. Both univariate and multivariate analyses were used. A p value of less than 0.05 was considered statistically significant. Results Most of the patients had poor sleep patterns (91%). It would appear that the main contributing factors are older age (p=0.009), self-rated health (p=0.001), anemia (p=0.002), excessive weight gain, and pain symptoms after dialysis session (p=0.001, p=0.001 respectively) and taking medications for sleep (p=0.016). Conclusion There is an extremely high level of poor sleep quality among patients on hemodialysis. The contributing factors are multifactorial. There is an urgent need to include sleep assessment, mental health screening, and psychosocial support education into the routine nephrology care program.